Inferring Biogeographic Ancestry and Its Use in Forensic Sciences - Bülbül, Özlem; Filoğlu, Gönül (The Bulletin of Legal Medicine, 2019)
In forensic applications SNP (Single nucleotide polymorphism) markers are used for identification, determination of phenotypes, lineage and ancestry. Ancestry informative SNP markers (AISNPs), which show differences between populations in different geographic regions, are used for estimating of the biogeographic ancestry. The biogeographical origin of a person and the percentage of genetic lineage taken from each biogeographic region can be determined using AISNP markers. This information may assist forensic investigations of unknown contributors or identification of missing persons and disaster victims. In this review, biogeographic ancestry concept, AISNPs panels used in estimation of the biogeographic ancestry, application methods, statistical methods, and current forensic applications has been discussed.